AB0642 Otolaryngeal Manifestations of Behçet's Disease in a Northern European Population. (9th June 2015) - Adeeb, F.; Conall, F.; Timon, C.; Shine, N.P.; Hughes, J.P.; Fraser, A.D.
Abstract : Background: The Otolaryngologic-related manifestations of Behçet's Disease (BD), though previously described, have been less thoroughly explored in the literature, particularly in a Northern European population. These manifestations are said to be relatively rare and include hearing loss, pharyngeal and laryngeal ulceration and nasal mucosal involvement. Objectives: The aim of this study was to undertake an assessment of a cohort of BD patients, documenting any laryngeal manifestations or evidence of reduced hearing. Methods: Patients meeting the International Study Group for Behçet's Disease (ISGBD) or the International Criteria for Behçet's Disease (ICBD) criteria for diagnosis were identified from an institutional database. Patients underwent assessment with an otolaryngologist, including flexible laryngoscopy. Intra-oral, pharyngeal and laryngeal manifestations of BD were documented and characterised. Patients underwent hearing assessment with pure-tone audiometry. Results: Fifteen BD patients were identified (4 male, 11 female; median age 36 years). 60% (n=9) showed evidence of disease on examination and flexible laryngoscopy. 33% (n=5) including two asymptomatic patients showed structural laryngeal changes related to BD. 13% (n=2) demonstrated bilateral, symmetrical sensorineural hearing loss. One patient warranted consideration for tracheotomy. Conclusions: Our cohort of BD patients demonstrate significant structural laryngeal changes, which appear to be more common than was previously thought. Therefore, raised awareness of the risk of laryngeal pathology in BD patients, including potential risk for later airway compromise, even in the absence of overt clinical symptomatology, and early screening may result in earlier diagnosis and treatment. Rheumatologists and Otolaryngologists should consider closer multi-disciplinary co-operation in the management and follow up of patients with BD. References: Webb CJ, Moots RJ, Swift AC. Ear, nose and throat manifestations of Behcet's disease: a review. The Journal of laryngology and otology. 2008 Dec;122(12):1279-83. PubMed PMID: 18616840. Gross M, Ben-Chetrit E. Laryngeal involvement in Behcet's disease–a challenge for treatment. Clinical rheumatology. 2013 Mar;32 Suppl 1:S75-7. PubMed PMID: 20532579. Cinar S, Cinar F, Kiran S. Is there a need for audiologic evaluation in patients with Behcet disease? Ear, nose, & throat journal. 2012 Mar;91(3):E15-9. PubMed PMID: 22430342. Disclosure of Interest: None declared